Optimization of the extraction process parameter for kenaf seeds oil to obtain high oil yield - Amid, Azura; Jamal, Parveen; Mohamad, Nurul Elyani; Engku Abdullah, Engku Hasmah (IIUM Press, 2011)
Kenaf (Hibiscus cannabinus) from the family of Malvaceae is a valuable fibre plant native to India and Africa. Kenaf is composed of various active components including tannins, polyphenolics, alkaloids, essential oils and steroids. In this study, kenaf seeds variety Khon kaen was used as a material in finding the optimum parameter in extracting seed oil that give the highest oil yield. Seeds were extracted using Soxhlet (control) and Supercritical Fluid Extractor (SFE). Extraction was performed at different temperature (40 to 80°C) and pressure (200 to 600 bars), respectively. Among these two parameters, temperature at 60°C shows the highest impact on the oil yield while the pressure at 600 bar is still not enough to obtain high oil yield.